EFFECTIVENESS SCIENCE LEARNING INNOVATION THROUGH ANDROID-BASED LEARNING MEDIA AND WATER PURIFICATION PRACTICE WITH PROBLEM-BASED LEARNING MODELS - Vita Kartika Arum; Marisa Christina Tapilouw; Sucahyo Sucahyo (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
Sustainable Development Goals (SDGs) is the United Nations’ effort to ensure that by 2030 all people in the world can enjoy peace and prosperity. One of the SDGs goals is clean water and sanitation. This provides opportunities for science learning innovation. The development of IT can make learning interesting and improve academic performance. This provides an opportunity to develop Learning Media which is an android operating system. The objective of this study is to analyse the effectiveness of the development of learning media in Indonesian Ecology and Biodiversity material that is integrated with SDGs, and test its effectiveness. The study wasne in class VII at the even by using research and development method with 4D (define, design, develop, dissemination). The result of the study from the ”define” stage, science learning in the form of Android Powerpoints and water purification practice had to potential to develop. In the “design” stage, learning media design using Water Biota’s theme and turquoise green background, black font, and font size that adjusts with layout size. In the “develop” stage, the score of media feasibility was 8 (valid) and material feasibility was 8.56 (valid). The score of the water purification device was 9.22 (valid). In the “disseminate” stage, the achievement of knowledge is measured from the results of pre-test (58.8) and post-test (68.8). The N-Gain score of the test was 0.23. From the result, the score of student worksheets was 94.34 and practice was 78.03. Finally, the innovations through Android-based learning and water purification practices were effective (> 3.40).